(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2018)
Magnetite (Fe3O4) nanoparticles were synthesized by sol-gel method using ferric nitrate and ethylene glycol as precursors at 250ºC and 300ºC. X-ray diffraction (XRD) study was used to determine the particle size and structural properties. The microstructural and particle size analysis were carried out using scanning electron microscope (SEM). Magnetite (Fe3O4) nanoparticles were annealed at 250ºC obtained as smaller crystal size than that of 300ºC. Fourier Transform Infrared (FTIR) spectroscopy was used to identify the functional groups of active compound in synthesized magnetite nanoparticles and their corresponding bands were observed in the region between 500cm-1 and 4000cm-1 of infrared radiation. The observed peaks at wave number 574cm-1 and 424cm-1 due to the vibration of tetrahedral and octahedral sites which is indicative the formation of spinel structure of magnetite (Fe3O4). Removal of Cr was found 80% by the synthesized magnetite (Fe3O4) nanoparticles 25g/L at pH 4.0 and contact time was 250 minutes. The results showed that prepared magnetite (Fe3O4) nanoparticles can be used for the treatment of wastewater containing chromium. Bangladesh J. Sci. Ind. Res.53(3), 219-224, 2018